Undang-Undang Nomor 32 Tahun 2009 tentang PPLH sebagai Instrumen Pembatasan Pemanfaatan SDA dalam Perspektif Maqāṣid al-Syarī‘ah - Upi Sopiah Ahmad; Pagar Hasibuan; Hasan Matsum; Fauziah Lubis (Kartika: Jurnal Studi Keislaman, 2025)
The utilization of natural resources in development practices often leads to environmental pollution and degradation when legal limitations are understood merely in procedural and administrative terms. Law Number 32 of 2009 on Environmental Protection and Management positions environmental planning as the foundation of environmental governance, particularly through the provisions of Article 10. However, this provision is still frequently interpreted in a formalistic manner, resulting in the underutilization of its normative function as an instrument for limiting natural resource exploitation. This article aims to analyze the position of Article 10 of Law No. 32 of 2009 from the perspective of maqāṣid al-syarī‘ah, with an emphasis on the principle of preventing harm (dar’ al-mafāsid), in order to reaffirm the orientation toward environmental protection and human safety. This study employs a normative legal research method using statutory and conceptual approaches. Primary legal materials consist of Law No. 32 of 2009, particularly Article 10, examined alongside relevant Islamic legal sources and supported by maqāṣid literature and contemporary environmental law studies as secondary materials. The findings indicate that Article 10 functions not merely as an administrative planning norm, but also contains preventive values aligned with the objectives of maqāṣid al-syarī‘ah, particularly the protection of life and public welfare.